1999
DOI: 10.1097/00007890-199907270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss and Fracture After Lung Transplantation1

Abstract: We conclude that fractures are a significant problem in the first year after lung transplantation, even in patients who receive therapy to prevent bone loss. Women with low pretransplantation BMD and a history of pretransplantation glucocorticoid therapy are at greatest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 32 publications
0
43
0
3
Order By: Relevance
“…Interestingly, the prevalence of morbidities related to immunosuppression in our 10-year survivors did not exceed that reported in patients earlier in the post-transplant course probably as a result of more intense immunosuppression in the early post-transplant period (14,(16)(17)(18)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 44%
“…Interestingly, the prevalence of morbidities related to immunosuppression in our 10-year survivors did not exceed that reported in patients earlier in the post-transplant course probably as a result of more intense immunosuppression in the early post-transplant period (14,(16)(17)(18)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 44%
“…43 Finally, the higher rates of fracture following cardiac and lung transplantation, for which higher doses of glucocorticoids are generally used, would be consistent for a pathogenetic role of glucocorticoids. 19,44,45 Other Immunosuppressive Agents A number of immunosuppressive agents used in transplantation have been shown to have adverse effects on bone in rodents, inducing a high turnover state and reducing bone mass; these include cyclosporine A, tacrolimus and cyclosporine G. 46 The effects of these agents in humans are difficult to study because these drugs are so rarely used in isolation and usually against a background of disease that itself affects bone remodelling, but small studies indicate similar effects in humans to those observed in rats. 47,48 More recently developed immunosuppressive agents include sirolimus and mycophenylate mofetil.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…We have previously reported that steroid withdrawal in patients who have undergone a successful liver transplant accelerates the recovery of lumbar spine bone density without adverse effects on graft tolerance (Martínez Díaz-Guerra et al, 2002). Moreover, higher rates of fracture occurring after cardiac and lung (Shane et al, 1999) transplantation, in which higher doses of steroids are use, would be consistent with their role in the pathogenesis of post transplant osteoporosis. The late phase observed in the postrasplant period takes place when the glucocorticoid doses are usually tapered below 5 mg per day.…”
Section: Related To Transplantation: Immunossupressor Drugs and Othermentioning
confidence: 70%